2012
DOI: 10.1007/s11368-012-0505-1
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acids in Lake Aydat catchment soils (French Massif Central): sources, distributions and potential use as sediment biomarkers

Abstract: International audiencePurpose: Eighteen soils were sampled in the Lake Aydat catchment in order to analyse free fatty acid (FA) content; FAs are considered to be among the most amenable biomarkers to mobilisation by runoff waters. The majority of the study area has soil cover consisting of grasslands or forest since the 2nd World War, although some covers having changed more recently. Material and methods: The soil studied all developed on volcanic rocks (andisols). The bulk organic matter (OM) content of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 73 publications
(84 reference statements)
4
20
0
Order By: Relevance
“…a rather low degree of OM preservation. This is consistent with a previous analysis of this sample which revealed a high content of free fatty acids (FAs) indicative of a release of these compounds by hydrolysis of plant esters (Zocatelli et al, 2012). Comparison of Sf and Spf showed that the latter displayed a higher TOC value associated with a lower pH.…”
Section: Bulk Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…a rather low degree of OM preservation. This is consistent with a previous analysis of this sample which revealed a high content of free fatty acids (FAs) indicative of a release of these compounds by hydrolysis of plant esters (Zocatelli et al, 2012). Comparison of Sf and Spf showed that the latter displayed a higher TOC value associated with a lower pH.…”
Section: Bulk Analysissupporting
confidence: 91%
“…HI values of the sub-surface samples (2-4 cm) were similar to those of other samples from the catchment (Zocatelli et al, 2012), but were quite low when compared with the large soil sample set studied by Disnar et al (2003). However, as pointed out by the latter authors, HI values are largely dependent on local vegetation.…”
Section: Bulk Analysissupporting
confidence: 75%
See 1 more Smart Citation
“…The standard was n° 160.000 (Vinci Technologies) and device precision was +/-3%. Details of the methodology of the temperature program have been described by Zocatelli et al (2012a Organic petrography extracts were prepared as described by Zocatelli et al (2012b).…”
Section: Core Descriptionmentioning
confidence: 99%
“…DOC and other bile acids have been lar gely st udied in wat er , sewage and sur ficial est uar ine sediment s t o evaluat e faecal pollut ion and det er mine it s sour ce (Elhmmali et al, 1997;Bull et al, 2002;Tyagi et al, 2008). They have also been st udied in ant hr opogenic and past ur e soils (Zocat elli et al, 2012). Bile acids ar e spar sely r epor t ed, however , in ancient envir onment al samples and wer e det ect ed in ar chaeological cont ext s such as ant hr opogenic manur e palaeosoils (Bull et al, 1999) and Neolit hic copr olit es (Shillit o et al, 2011).…”
Section: Resul T S and Discussionmentioning
confidence: 99%